Q:

Find the derivative of f(x) = 12x^2 + 8x at x = 9.

Accepted Solution

A:
Answer:224Step-by-step explanation:We will need the following rules for derivative:[tex](f+g)'=f'+g'[/tex] Sum rule.[tex](cf)'=cf'[/tex] Constant multiple rule.[tex](x^n)'=nx^{n-1}[/tex] Power rule.[tex](x)'=1[/tex] Slope of y=x is 1.[tex]f(x)=12x^2+8x[/tex][tex]f'(x)=(12x^2+8x)'[/tex][tex]f'(x)=(12x^2)'+(8x)'[/tex] by sum rule.[tex]f'(x)=12(x^2)+8(x)'[/tex] by constant multiple rule.[tex]f'(x)=12(2x)+8(1)[/tex] by power rule.[tex]f'(x)=24x+8[/tex]Now we need to find the derivative function evaluated at x=9.[tex]f'(9)=24(9)+8[/tex][tex]f'(9)=216+8[/tex][tex]f'(9)=224[/tex]In case you wanted to use the formal definition of derivative:[tex]f'(x)=\lim_{h \rightarrow 0} \frac{f(x+h)-f(x)}{h}[/tex]Or the formal definition evaluated at x=a:[tex]f'(a)=\lim_{h \rightarrow 0} \frac{f(a+h)-f(a)}{h}[/tex]Let's use that a=9.[tex]f'(9)=\lim_{h \rightarrow 0} \frac{f(9+h)-f(9)}{h}[/tex]We need to find f(9+h) and f(9):[tex]f(9+h)=12(9+h)^2+8(9+h)[/tex][tex]f(9+h)=12(9+h)(9+h)+72+8h[/tex][tex]f(9+h)=12(81+18h+h^2)+72+8h[/tex] (used foil or the formula  (x+a)(x+a)=x^2+2ax+a^2)[tex]f(9+h)=972+216h+12h^2+72+8h[/tex]Combine like terms:[tex]f(9+h)=1044+224h+12h^2[/tex][tex]f(9)=12(9)^2+8(9)[/tex][tex]f(9)=12(81)+72[/tex][tex]f(9)=972+72[/tex][tex]f(9)=1044[/tex]Ok now back to our definition:[tex]f'(9)=\lim_{h \rightarrow 0} \frac{f(9+h)-f(9)}{h}[/tex][tex]f'(9)=\lim_{h \rightarrow 0} \frac{1044+224h+12h^2-1044}{h}[/tex]Simplify by doing 1044-1044:[tex]f'(9)=\lim_{h \rightarrow 0} \frac{224h+12h^2}{h}[/tex]Each term has a factor of h so divide top and bottom by h:[tex]f'(9)=\lim_{h \rightarrow 0} \frac{224+12h}{1}[/tex][tex]f'(9)=\lim_{h \rightarrow 0}(224+12h)[/tex][tex]f'(9)=224+12(0)[/tex][tex]f'(9)=224+0[/tex][tex]f'(9)=224[/tex]